Influence of the duration of noninvasive ventilation on the cardiorespiratory indicators of preterm infants: A randomized clinical trial - Carmen Silveira ST; Kamila Leonardi M; Ana Paula Melo CF; José Zaia E; Marisa Brunherotti AA (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2018)
This study aimed to evaluate the cardiorespiratory indicators of preterm infants submitted to two noninvasive ventilator support systems in two periods. It was an controlled randomized clinical trial (RBR-7d9dth). Fifty-two newborns (gestational age of 30.6±2.3 weeks, weight of 1,366±445 g) submitted to continuous positive airway pressure (CPAP) therapy were studied. The infants were randomly allocated to two groups: 31 children received CPAP therapy for 48 hours and 21 children for 72 hours. The respiratory rate, heart rate, oxygen saturation and Silverman-Andersen Score were recorded once a day. Three measurements were obtained in a 15 minutes intervals. The infants were monitored during the predetermined period of noninvasive ventilation and for 24 hours after pressure support withdrawal. The Student t-test was used for comparison of the variables between groups after normality evaluation by the Kolmogorov-Smirnov test and significance was considered when p<0.05. It was found that the birth characteristics were homogenous, without significant differences between groups. The cardiorespiratory indicators did not differ significantly between groups, but better mean values were observed for the 72-hour group. There was a difference in the respiratory rate of 5.0 breaths per minute and the heart rate was 7.8 bpm, while oxygen saturation was similar in the two groups.  Conclusions: Neither the duration of noninvasive ventilation of 48 or 72 hours nor the nasal CPAP and nasal intermittent positive pressure had an influence on the cardiorespiratory indicators of preterm infants. However, the period of 72 hours resulted in lower respiratory and heart rates.